2017
DOI: 10.1007/s10862-017-9595-9
|View full text |Cite
|
Sign up to set email alerts
|

Initial Psychometric Validation of the Non-Suicidal Self-Injury Scar Cognition Scale

Abstract: Given the growing literature on the detrimental psychological consequences of NSSI, it is surprising that scarce research has focused on the permanent physical consequences of NSSI, scarring to one’s tissue (Burke et al. 2015; Lewis 2016). Indeed, with recent research suggesting that upwards of half of those with a history of NSSI bear scarring as a result of the behavior (Burke et al. 2016), the psychological implications of scarring are important to understand. Given preliminary literature suggesting that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 61 publications
1
32
1
Order By: Relevance
“…Although scarring is a well-known direct consequence of NSSI, relatively few empirical studies have systematically examined its psychosocial consequences and correlates. Extant research suggests that individuals with NSSI scarring often report negative cognitions about their scars and associated feelings of shame and embarrassment (Bachtelle & Pepper, 2015; Burke, Olino, & Alloy, 2017; Lewis & Mehrabkhani, 2016). Burke and colleagues (2017) found that those who reported greater negative socially-related cognitions (e.g., shame, embarrassment) about their scars exhibited higher levels of social anxiety, depression, and suicidal ideation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although scarring is a well-known direct consequence of NSSI, relatively few empirical studies have systematically examined its psychosocial consequences and correlates. Extant research suggests that individuals with NSSI scarring often report negative cognitions about their scars and associated feelings of shame and embarrassment (Bachtelle & Pepper, 2015; Burke, Olino, & Alloy, 2017; Lewis & Mehrabkhani, 2016). Burke and colleagues (2017) found that those who reported greater negative socially-related cognitions (e.g., shame, embarrassment) about their scars exhibited higher levels of social anxiety, depression, and suicidal ideation.…”
mentioning
confidence: 99%
“…Extant research suggests that individuals with NSSI scarring often report negative cognitions about their scars and associated feelings of shame and embarrassment (Bachtelle & Pepper, 2015; Burke, Olino, & Alloy, 2017; Lewis & Mehrabkhani, 2016). Burke and colleagues (2017) found that those who reported greater negative socially-related cognitions (e.g., shame, embarrassment) about their scars exhibited higher levels of social anxiety, depression, and suicidal ideation. Other literature has found that NSSI scars are associated with significantly elevated levels of negative body image, including lower appearance evaluation and body area satisfaction (Dyer, Hennrich, Borgmann, White, & Alpers, 2013; Dyer, Mayer-Eckhard, White, & Alpers, 2015).…”
mentioning
confidence: 99%
“…Specific to NSSI, there is accumulating evidence that individuals with scarring report feeling shame and embarrassment about their scarring (Bachtelle & Pepper, 2015; Burke, Olino, & Alloy, 2017; Lewis & Mehrabkhani, 2016), providing complementary evidence of self‐stigma. Additionally, people who engage in NSSI may be hesitant to disclose a history of NSSI due to a perceived likelihood of a negative reaction (Berger, Hasking, & Martin, 2013), such as being labeled as attention seeking (Fortune, Sinclair, & Hawton, 2008; Klineberg, Kelly, Stansfeld, & Bhui, 2013).…”
Section: Current Studymentioning
confidence: 99%
“…A total of 1501 students were recruited, of whom 1193 were eligible. In order to receive reimbursement, participants were informed that they needed to complete all cognition tests and 60% of the triweekly alcohol consumption questions, which is a common compliance cut-off [22] and comprises in this study at least 7 out 12 responses during each four-week period. These criteria were met by 702 participants at Wave 1 and by 436 participants at Wave 2 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…These criteria were met by 702 participants at Wave 1 and by 436 participants at Wave 2 (Figure 1). compliance cut-off [22] and comprises in this study at least 7 out 12 responses during each four-week period. These criteria were met by 702 participants at Wave 1 and by 436 participants at Wave 2 ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%